Challenges Of Rural Women In Agricultural Production And Food Sufficiency In Cross River State, Nigeria - Agbor, Uno Ijim; Eteng, Felix Onen (Advances in Social Sciences Research Journal, 2019)
This study focuses on the involvement of women in agricultural production in Cross River State, Nigeria. The objective is to ascertain the contributions of women to food sufficiency in the state and the challenges they face in course of their farming process. The study attempted to answer the following research questions; what is the level of contribution of women in agriculture to food sufficiency in Cross River State? What are the inhibiting challenges to agricultural production by women in Cross River State? A total of 900 women across the State were examined to capture their involvement and contribution to agricultural production as well as the challenges they face in this process. Data was generated through questionnaire, interview and observation and were analyzed with simple percentage technique and presented on tables and graph. The study discovered that women in agriculture in cross river are active contributors to food sufficiency through the remarkable increase in their crop production index. Second; women are faced with challenges that inhibit robust food production in the state such as land restriction, limited access to capital/access to credit, gender inequality/discrimination and lack of storage facility. On the basis of this the study advocates policy change to give women access to more land and credit facilities. Traditional norms that hinder women access to land be relaxed through government conscious pressure on local culture. Robust assistance to fund women agriculture should become the priority of the state and the local governments through conscious policy of soft credit facilities with minimal collateral.